Memberikan Pendidikan Pentingnya Ilmu Komputer dan Manajemen, Semangat Anti Narkoba dan Berprestasi Siswa di Masa Pandemi untuk Masa Depan yang Gemilang di SMAN 2 Medan - Mira Yosefa Siregar (LPPM Universitas KH. A. Wahab Hasbullah, 2022)
Education Computing and management knowledge is very important related to the human ability to access the internet and self-management to know about the dangers of drugs as early possible we inform children, students and neighbors in the surrounding environment that drugs have a negative impact on human health and survival, there are many types of drugs that have been circulating throughout Indonesia which are not only consumed by the public, artists , government officials and even state official of areas North Sumatra. This is very influential and has a negative impact on the development of self and the soul of adolescent children characterized by frequent truancy during study hours, often sleepy while studying in class, declining grades because they do not care about school and never study again, changes in attitudes and personality such as irritability , likes to steal justifies all means and does not care about personal health. Meanwhile, the dangers for students in the short term when consuming illegal drugs are characterized by increased heart rate, sleeplessness or insomnia, no appetite, unclear speech, changes in cognitive abilities, and a sense of euphoria and loss of coordination of the student's body parts if consuming drugs this means it can damage the moral life of the younger generation. The population in this service is 33 students majoring in social studies with the technique of determining the choice is the census technique. Data collection by interview, question and answer and documentation.